Does Judge Has Ex Officio Rights In determining Mut’ah and Iddah? - Sri Turatmiyah; Muhammad Syaifuddin; Annalisa Yahanan; Febrian Febrian; Arfianna Novera (Faculty of Law, Sriwijaya University, Indonesia, 2019)
The research aims to analyze the factors why the Religious Court judges do not use their ex officio rights in divorce lawsuits. In divorce case, the defendant who does not have any knowledge about divorce laws generally does not ask for mut'ah and iddah to the plaintiff. The question of this research is what factors caused the judges of Religious Court in South Sumatera, especially Palembang and Kayuagung do not exercise the ex officio rights in determining the quality of mut'ah and iddah due to divorce. This research used normative juridical method with empirical juridical through statute approach and case approach. The results show that during 2017 the Religious Court of Palembang used only once its ex officio rightwhile the Religious Court of Kayuagung did it three times. The reasons are: the judges grant only the petitum of the petitioner solely for the reason that the defendant party does not file a counter-claim, in which judge’s reasoning is based on Article 178 paragraph (3) HIR/189 paragraph (3) RBG that the judge is prohibited from giving a verdict which is more than being petitioned known as the ultra petitum partium, the wife's side as the defendant never attended the hearing, the wife never gave an answer or response to the argument in the application of the plaintiff, the wife was not present in the verdict (verstek), the wife of nusyuz, (does not do her duties as wife) the husband is economically insufficient, the wife does not want to demand the maintenance of mut'ah and iddah, the judge sees the causality. This study suggests that judges should exercise their ex officio rights and give advice as well sufficient information to the wife in order to fulfill her rights and interests as the result of the divorce.